Investigation of Factors Influencing Dispersion of Liquid Hydrocarbons in Porous Media - Hussain Ali Baker, Lecturer (Journal of Engineering, 2016)
An experimental work has been done to study the major factors that affect the axial dispersion of some hydrocarbons during liquid-liquid miscible displacement. Kerosene and gas oil are used as displacing phase while seven liquid hydrocarbons of high purity represent the displaced phase, three of the liquids are aromatics and the rest are of paraffinic base. In conducting the experiments, two packed beds of different porosity and permeability are used as porous media.